A Case Study of a Plant-Animal Relationship: Cola lizae and Lowland Gorillas in the Lope Reserve, Gabon - Tutin, C. E. G.; Williamson, E. A.; Rogers, M. E.; Fernandez, M. (1991)
The fruits of Cola lizae, an endemic tree with a limited geographical distribution, have been a major food source for lowland gorillas in the Lope Reserve during part of each year over a six-year period. Faecal analysis indicated that 11,000-18,000 Cola seeds km-2 were deposited by gorillas during the 4-month season in 1989. Gorillas are the only important dispersers of this species: other primates consume the succulent mesocarp, but do not swallow the large seed; elephants do not eat Cola fruits. Observations of Cola seeds in gorilla faeces showed a very high germination rate and, despite initial high mortality, 18% of seedlings still survived six months after deposition. Survival of seedlings was significantly better in faeces left at nest-sites than in other areas of the forest: 40% of seedlings were viable at nest-sites six months after deposition. This suggests that the open areas of forest, preferred by gorillas as nest-sites, are advantageous to the propagation of this species.